Households with Fibre Reinforced Composite BIPV modules in Southern Europe under Net Metering Scheme. (July 2019) - Kyritsis, A.; Roman, E.; Kalogirou, S.A.; Nikoletatos, J.; Agathokleous, R.; Mathas, E.; Tselepis, S.
Abstract: In recent years many Renewable Energy Sources (RES) power plants have been connected to power networks throughout Europe, in order to meet the EU's objectives for sustainable energy supply. As far as RES residential applications are concerned, the grid-connected photovoltaic (PV) systems constitute the most important representative of RES, because PVs can be easily installed even in densely built-up areas. In this context, small residential PV systems utilising Building Integrated PV (BIPV) modules are going to gain ground mainly at newly built or rebuilt building structures. That is because a BIPV module operates as a multi-functional building construction material; it generates energy and serves as part of the building envelope. This paper highlights the energy benefits of residential buildings in Southern Europe with Fibre Reinforced Composite BIPV modules under Net Metering Scheme and proposes suitable grid-connected PV inverter structures in case of BIPV systems with multiple orientation and inclination profiles. Highlights: Fibre Reinforced Composite BIPV modules suitable for residential buildings. PV inverter structures for BIPV systems with multiple orientation profiles. BIPVs with multiple orientation profiles address well the energy needs of residences. BIPVs with multiple orientation profiles lead to high PV system output self-utilization. BIPVs with multiple orientation profiles lead to considerable IRR values in Southern Europe.